Correlation of sp2 carbon bonds content in magnetron-sputtered amorphous carbon films to their electrochemical H2O2 production for water decontamination applications. (November 2015) - Pandiyan, R.; Delegan, N.; Dirany, A.; Drogui, P.; El Khakani, M.A.
Abstract: The radio frequency (RF)-magnetron sputtering technique was used to deposit amorphous carbon (a-C) films onto different substrates at different deposition substrate temperatures ( Td ) ranging from room temperature (RT) to 750 °C. The carbon bonding states of the a-C films were systematically investigated by means of Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) as a function of Td . The Raman analyses clearly show that an increase of Td leads to significant microstructural changes of the initially mixed sp 2 /sp 3 carbon bonds, for the films deposited at RT into a more graphitic like sp 2 bonding at higher Td . This increase of [sp 2 ]-bonded fraction of carbon atoms to the detriment of the sp 3 bonded ones has been quantitatively confirmed by the XPS carbon C 1s core level spectra analyses. Indeed, the sp 3 -bonds content of the a-C films is found to diminish from 44% at RT to a minimum value of 16% around Td = 450 °C and then stabilizes around 26% at Td = 750 °C. On the other hand, the hydrogen peroxide (H2 O2 ) production capacity of these a-C films was systematically evaluated, and found to reach its maximum of 11.2 μg/L/cm 2 at Td = 450 °C, at which the highest C sp 2 -bonds content was also observed. We were thus able to point up, for the first time, a fairly linear correlation between the produced amount of H2 O2 of the a-C films and their relative [sp 2 ] bonding content, over an [sp 2 ] relative content range as wide as (0–84%). These results clearly demonstrate the relevance of a-C films with a pronounced graphitic like character for H2 O2 production. Such a-C cathodes with an enhanced H2 O2 production capacity are highly sought for in electrochemical decontamination of water from persistent organic pollutants.